Therapeutic Management Of Haemoprotozoan Infections With Reference To Haematological Changes In Canines And Bovines - Dabas, V. S.; Bhatt, R. H.; Suthar, D. N.; Jhala, S. K.; Chaudhari, C. F.; Patel , J. M. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Of 260 cases of bovines and canines suspected for haemoprotozoan infection, reported at Teaching Veterinary Clinical Complex, Veterinary College, N.A.U., Navsari from March, 2011 to February, 2012, 60 animals were found positive for different haemoprotozoan infections viz., babesiosis, anaplasmosis, trypanosomiasis, theileriosis and mixed infections. Haematological examination and smear examinations were carried out in all suspected animals. Confirmed cases were treated with three different treatment groups and recovery was analyzed on the basis of improvement in blood picture. Combination of Inj. Oxytetracycline and Inj. Diamenazine Aceturate was found effective among all three treatment groups.
Keywords: Haemoprotozoa; Canine; Bovine